Treatment and outcome of 432 patients with extensive-stage small cell lung cancer in first, second and third line – Results from the prospective German TLK cohort study. (April 2019) - Steffens, Claus-Christoph; Elender, Corinna; Hutzschenreuter, Ulrich; Dille, Stephanie; Binninger, Adrian; Spring, Lisa; Jänicke, Martina; Marschner, Norbert; ,
Highlights: Real-world data on the treatment of 432 patients with extensive-stage SCLC in Germany. 93% of the patients received first-line platinum-based combination chemotherapy. Carboplatin or cisplatin combinations yielded similar response and survival rates. 50% of the patients received a second and 22% a third line of treatment. 77% of the patients in routine care would be eligible for a clinical trial. Abstract: Objectives: Despite intensive research, the therapeutic options in extensive-stage small cell lung cancer (SCLC) are still limited. Data from routine clinical practice, so-called "real-world data", are centrally important to assess and improve the standard of care. We present prospectively documented data on systemic first-, second- and third-line treatment, number of treatment lines and outcome parameters of patients treated by medical oncologists in Germany. Materials and methods: This is a descriptive analysis on 432 patients with extensive-stage SCLC enrolled at start of first-line therapy into the prospective German clinical cohort study TLK (Tumour Registry Lung Cancer). Patients were recruited by 87 sites between February 2010 and December 2013 and followed-up individually for 3 years. Results: The majority of patients (93%) received a first-line platinum-based combination therapy. Carboplatin plus etoposide was documented more frequently than cisplatin plus etoposide (46 vs. 35%); patients receiving carboplatin were older (68 vs. 63 years) and more often presented with poorer performance status (17 vs. 11% ECOG ≥ 2). Both regimens yielded similar response and survival rates. Median first-line overall survival (OS) was 10.2 months (95% confidence interval [CI] 8.6–12.3) for carboplatin plus etoposide and 12.2 months (95% CI 10.1–14.7) for cisplatin plus etoposide. Most patients (77%) would have been eligible for participation in a clinical trial. 50% of the patients received a second and 22% a third line of treatment. Median second-line OS was 5.8 months (95% CI 4.8–7.5), median third-line OS 5.7 months (95% CI 3.8–7.0). Conclusion: To our knowledge, this is the first study of prospectively documented patients with extensive-stage SCLC in routine clinical practice. We present treatment algorithms as well as outcome parameters for a large cohort in first-, second- and third-line treatment. The survival times and response rates reported in this routine setting correspond to the respective measures from large prospective trials.